INCREASING ATMOSPHERIC CONCENTRATIONS OF LONG-LIVED HALOCARBONS AND METHANE - マキデ, ヨシヒロ; クボ, ユウジ; トミナガ, タケシ; MAKIDE, Yoshihiro; KUBO, Yuji; TOMINAGA, Takeshi (National Institute of Polar Research, 1987)
P(論文) A great concern has been indicated again about the increasing atmospheric concentrations of long-lived anthropogenic halocarbons regarding the "ozone hole" observed recently over Antarctica, and the increase in atmospheric methane concentration has also received a great attention because of its "greenhouse effect" in addition to the effect by CO_2. We have been measuring atmospheric concentrations of those halocarbons (CCl_2F_2,CCl_3F, CH_3CCl_3,etc.) and methane (CH_4) in Antarctica as well as in the Northern Hemisphere (N. H.) in order to clarify behaviors of these compounds in the atmosphere and to estimate future trends of concentrations and their effects on the earth's environment. Surface-level samples in Antarctica have been collected (since 1982) at 500-1000m NE of Syowa Station into all-stainless steel sample canisters which had been prepared in extremely clean conditions and evacuated for grab-sampling. All the Antarctic samples have been analyzed after 3-15 months at University of Tokyo by ECD gaschromatography (for halocarbons) and by FID gaschromatography (for methane). Averaged concentrations in the mid-latitude N. H. have been obtained (since 1979) by analyzing the samples collected in Hokkaido (42-45°N) every summer (July-August) and winter (January-February). The CCl_2F_2 and CCl_3F concentrations observed in Antarctica have been 8-10% lower than those observed in Hokkaido in accordance with the predominant emission of these halocarbons in the N. H. and their delayed diffusion into the Southern Hemisphere across the Intertropical Convergence Zone. The concentration of CH_3CCl_3 has been about 30% lower in Antarctica in accordance with its relatively short atmospheric lifetime (about 6 years) due to the reaction with tropospheric OH radicals. The atmospheric concentrations of CCl_2F_2 and CCl_3F have been increasing steadily (almost linearly) in both hemispheres (by 4-5% every year). These increments of CCl_2F_2 and CCl_3F concentrations correspond to their unchanged or rather increasing ...